Информационная система мониторинга здоровья студентов - Берестнева О. Г. Ольга Григорьевна; Иванов В. Т.; Иванкина Л. И. Любовь Ивановна; Шаропин К. А. Константин Александрович; Муратова Е. А. Елена Анатольевна (2002, 2002)
В фонде НТБ ТПУ отсутствует